The rare gem that is Armstrong - Abd Razak, Dzulkifli (2009)
THERE was something conspicuously missing in the 40th anniversary celebration of the lunar landing last month: Neil Armstrong. The first man on the moon was not much seen during the commemorative celebrations, at least relative to his colleague, Edwin "Buzz" Aldrin. The lunar landing was, perhaps, one of the greatest human feats of the last century, and Armstrong was the man at the centre of it all.